Use of a smartphone ECG to diagnose arrhythmias in athletes: a case series - Jewson, J.; Orchard, J.; Semsarian, C.; Fitzpatrick, J.; La Gerche, A.; Orchard, J. (EP Europace, 2021)
Background: While athletes are generally very fit, intense exercise can increase the risk of atrial fibrillation (AF), resulting in distressing symptoms during or after exercise. Moreover, other arrhythmias such as atrial flutter or supraventricular tachycardia (SVT) can also cause troublesome, exercise-related symptoms. Accurate diagnosis is essential to guide appropriate treatment. Given the symptoms are infrequent and/or occur in specific circumstances, traditional monitoring devices are often impractical to use during exercise or too invasive. Recently, smartphone ECGs such as the Alivecor KardiaMobile device (iECG) has been shown to be interpretable by a cardiologist in 95% of cases and may be the portable tool required to help identify arrhythmias in this challenging population. Purpose: This case series was designed to highlight the use of iECG devices in aiding the diagnosis of arrhythmias in exercise-related symptoms. Methods: Five cases are reported where the iECG was used to document at least one episode of exercise-related symptoms. Participants were eligible if they were over 18 years of age and had had an iECG trace taken during an episode of exercise-related symptoms (e.g. light-headedness, shortness of breath, palpitations). which could be associated with an arrhythmia All participants were identified by authors from previous clinical experiences (or from clinical colleagues) and provided written, informed consent. Results: The cases included one amateur middle-distance runner in his 40s, two amateur ultra-endurance runners in their 30s and two young elite cricketers (Figure 1). In four of the cases, an accurate diagnosis of an arrhythmia (atrial flutter, AF and 2x SVT) was obtained using the iECG device, which helped to guide definitive treatment (e.g. medication or ablation). Two of these cases had been investigated using traditional methods such as stress ECG or Holter monitor over many months without achieving a diagnosis. The final case did not obtain a cardiac diagnosis using the iECG device despite using it on multiple occasions during symptomatic events. This reassured this athlete that the symptoms experienced were not cardiac related and she is now confident to exercise. Conclusion: The iECG was able to accurately detect arrhythmias and provide a diagnosis in cases where traditional monitoring had not. The utility of detecting no arrhythmia during symptoms in one case was also highlighted, providing the athlete with the confidence to continue exercising. This reassurance and confidence across all cases is perhaps the most valuable aspect of this device, where clinicians and athletes can be more certain of reaching a diagnosis and undertaking appropriate management.